2017
DOI: 10.3390/ijms18061295
|View full text |Cite
|
Sign up to set email alerts
|

EGFR and EGFRvIII Promote Angiogenesis and Cell Invasion in Glioblastoma: Combination Therapies for an Effective Treatment

Abstract: Epidermal growth factor receptor (EGFR) and the mutant EGFRvIII are major focal points in current concepts of targeted cancer therapy for glioblastoma multiforme (GBM), the most malignant primary brain tumor. The receptors participate in the key processes of tumor cell invasion and tumor-related angiogenesis and their upregulation correlates with the poor prognosis of glioma patients. Glioma cell invasion and increased angiogenesis share mechanisms of the degradation of the extracellular matrix (ECM) through u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
75
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 97 publications
(82 citation statements)
references
References 111 publications
(120 reference statements)
6
75
0
1
Order By: Relevance
“…The major reason that therapeutic treatments fail are due to the highly invasive nature of the tumor cells and the occurrence of increased angiogenesis [26]. GBM harbors a subpopulation of self-renewing, therapy-resistant cells, GICs.…”
Section: Discussionmentioning
confidence: 99%
“…The major reason that therapeutic treatments fail are due to the highly invasive nature of the tumor cells and the occurrence of increased angiogenesis [26]. GBM harbors a subpopulation of self-renewing, therapy-resistant cells, GICs.…”
Section: Discussionmentioning
confidence: 99%
“…This could be due to receptor interference and associations with multiple transduction pathways and proteins of invasion and angiogenesis regulation and the development of resistance mechanisms. Therefore, new therapies are focused on a combination of targeted gene therapy against EGFR and EGFRvIII and transduction pathways and proteins related to this pathway [22]. Recently new EGFR-targeted therapies have been proposed (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…The induction of neovascularization is a complex process that is dependent on multiple factors, including stem cells, intermediate signalling (nitric oxide‐cGMP), and growth factors (VEGF and EGF) . Signalling through EGFR is generally believed to be angiogenic in cancer . In our study, we found that injection of AG1478 (2 μg/μL, 2 μL) significantly reduced the formation of neovascular tufts (Figure D), indicating that EGFR signalling was causally linked to the development of neovascular tufts.…”
Section: Discussionmentioning
confidence: 99%